Functional characterization of methionine sulfoxide reductases from Leptospira interrogans - Sasoni, Natalia (2021)
Background: Methionine (Met) oxidation leads to a racemic mixture of R and S forms of methionine sulfoxide (MetSO). Methionine sulfoxide reductases (Msr) are enzymes that can reduce specifically each isomer of MetSO, both free and protein-bound. The Met oxidation could change the structure and function of many proteins, not only of those redox-related but also of others involved in different metabolic pathways. Until now, there is no information about the presence or function of Msrs enzymes in Leptospira interrogans. Methods: We identified genes coding for putative MsrAs (A1 and A2) and MsrB in L. interrogans serovar Copenhageni strain Fiocruz L1-130 genome project. From these, we obtained the recombinant proteins and performed their functional characterization. Results: The recombinant L. interrogans MsrB catalyzed the reduction of Met(R)SO using glutaredoxin and thioredoxin as reducing substrates and behaves like a 1-Cys Msr (without resolutive Cys residue). It was able to partially revert the in vitro HClO-dependent inactivation of L. interrogans catalase. Both recombinant MsrAs reduced Met(S)SO, being the recycle mediated by the thioredoxin system. LinMsrAs were more efficient than LinMsrB for free and protein-bound MetSO reduction. Besides, LinMsrAs are enzymes involving a Cys triad in their catalytic mechanism. LinMsrs showed a dual localization, both in cytoplasm and periplasm. Conclusions and General significance: This article brings new knowledge about redox metabolism in L. interrogans. Our results support the occurrence of a metabolic pathway involved in the critical function of repairing oxidized macromolecules in this pathogen.